Pengembangan E-modul berbasis PBL untuk meningkatkan keterampilan pemecahan masalah dan berpikir kritis siswa sekolah dasar - Ahdhianto, Erif; Masula, Siti; Thohir, M Anas; Khotimah, Khusnul (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This research goal is to determine whether there are eligible, practical, and effective problem-based learning e-modules for elementary students. This research was conducted with 5th grade students and teachers in Blitar City, which operates the Kurikulum Merdeka. This study used the ADDIE Model, which entails analyzing a learning need, producing content, developing learning items, putting the product model to the test on participants, and conducting an evaluation. Every stage involves doing observations, interviews, and tests to gather qualitative data for the analysis of any learning requirements. The e-modules product is tested practically using the two types of surveys, ARG and ARS, to determine its eligibility for test quiz skills, problem-solving abilities, and critical thinking. Descriptive analysis and inferential statistics will be used to analyze the data. The study's findings indicate that: (1) Problem-based learning e-modules are matched based on the evaluations of the designers' team and the expertise team. (2) The results of the ARG and ARS tests indicate that problem-based learning e-modules are more practical. (3) The paired sample t-test indicates that problem-based learning e-modules are effective in enhancing problem-solving and critical thinking abilities. There is a significant difference between learning with and without problem-based learning e-modules